2004
DOI: 10.1007/s10265-003-0134-2
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids in translucent bracts of the Himalayan Rheum nobile (Polygonaceae) as ultraviolet shields

Abstract: UV-absorbing substances were isolated from the translucent bracts of Rheum nobile, which grows in the alpine zone of the eastern Himalayas. Nine kinds of the UV-absorbing substances were found by high performance liquid chromatography (HPLC) and paper chromatography (PC) surveys. All of the five major compounds are flavonoids, and were identified as quercetin 3- O-glucoside, quercetin 3- O-galactoside, quercetin 3- O-rutinoside, quercetin 3- O-arabinoside and quercetin 3- O-[6"-(3-hydroxy-3-methylglutaroyl)-gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 22 publications
0
31
0
Order By: Relevance
“…Based on measurements on a single inflorescence on R. nobile in Nepal, Omori and Ohba (1999) reported that bracts on the inflorescence elevated the temperature of floral tissues and had insulative effects. In addition, the large bracts of R. nobile and R. alexandrae have positive effects on the control of sunlight penetration and protect the inflorescence from ultraviolet radiation (Terashima et al, 1993;Omori and Ohba, 1996;Omori et al, 2000;Tsukaya, 2002;Iwashina et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Based on measurements on a single inflorescence on R. nobile in Nepal, Omori and Ohba (1999) reported that bracts on the inflorescence elevated the temperature of floral tissues and had insulative effects. In addition, the large bracts of R. nobile and R. alexandrae have positive effects on the control of sunlight penetration and protect the inflorescence from ultraviolet radiation (Terashima et al, 1993;Omori and Ohba, 1996;Omori et al, 2000;Tsukaya, 2002;Iwashina et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…To the best our knowledge, this is the first report of the presence of an anthocyanin acylated with 3-hydroxy-3-methylglutaric acid in plants, although there are some reports on the distributions of flavones and flavonols acylated with this acid, such as in Citrus (Kumamoto et al, 1985;Horie et al, 1986), Rheum (Iwashina et al, 2004), et al, 1986), Viscum (Harborne and Baxter, 1999) and Frullania (Kraut et al, 1993). The occurrence of a new type of acylated anthocyanin provides further --6 interesting information for researchers in this field of chemistry.…”
Section: Discussionmentioning
confidence: 91%
“…A well-known case of translucent leaves in order to improve photosynthesis, to allow warming of the tissues and even to improve reproduction is that of the glasshouse plants of several Rheum species of the Himalayas. [19][20][21][22] While improving their survival and sexual reproduction by being translucent, these glasshouse plants decrease the danger of UV-B radiation damage by expressing high levels of flavonoids that absorb it. 21,22 Improving photosynthesis also seems to operate when the fast-growing young and partly transparent pods discussed here can perform photosynthesis in both external and internal layers.…”
Section: Resultsmentioning
confidence: 99%